Raloxifene suppress proliferation-promoting function of estrogen in CaSKi cervical cells - Ma, Jing-Quan (Int J Clin Exp Med, 2015)
Raloxifene has demonstrated anti-estrogen activity in reproductive organs and tissues, but there are very few related studies in cervical cells. The aims of this study is to explore the function of raloxifene in CaSKi cervical cells. We examined the effects of raloxifene on cervical cancer cells exposed to estrogen. The effect of Raloxifene on cell growth, apoptosis was detected. The human papillomavirus (HPV) 16 E6E7 transcription in cervical cell line CaSki cells exposed to 17-estradiol was also examined. Apoptosis was measured by endonucleolytic degradation of DNA. HPV 16 E6E7 was measured by northern analysis. The results indicated that raloxifine inhibits estrogenic promotion activity on growth of CaSki cells. Raloxifene suppresses the proliferation promotion activity of estradiol in CaSki cells. Raloxifene suppresses the stimulation effect of estradiol on HPV 16 E6E7 transcription in CaSki cells. In conclusion, raloxifene inhibit the CaSki cells proliferation induced by estradiol, which suggests that raloxifine also has anti-estrogen activity in cervical cells.